Comparison between shear wave elastography and serological findings for the evaluation of fibrosis in chronic liver disease - Liaqat Mahjabeen; Siddique Kashif; Yousaf Imran; Bacha Raham; Farooq S. Muhammad Yousaf; Gilani Syed Amir (Journal of Ultrasonography, 2021)
Aim: In this study, we sought to examine the optimal cutoff values for predicting different stages of liver fibrosis, and to determine the level of agreement between shear wave elastography and aspartate aminotransferase to platelet ratio index (APRI) and fibrosis-4 index (FIB-4) scores in patients with chronic liver disease. Methodology: A descriptive, cross-sectional study was performed at the Radiology Department of Shaukat Khanum Memorial Hospital Lahore from 1 Jun 2019 until 1 June 2020. FIB-4 and APRI scores were determined by the following formula: FIB-4 = (age × AST) ÷ (platelet count × (√ (ALT)) and APRI = (AST÷AST upper limit of normal) ÷ platelet × 100. Data was analyzed with the help of SPSS version 24.0 and Microsoft Excel 2013. Results: Eighty individuals were conveniently selected, of which 62.5% were men and 37.5% were women. The mean age of the subjects was 43.47 SD ± 13.85 years. APRI and FIB-4 scores predicted F4 patients using the cutoff values of 0.47 (Sn. 72%, Sp. 70%) and 1.27 (Sn. 78%, Sp. 73%), respectively. The cutoff values of 0.46 for APRI and 1.27 for FIB-4 predicted F3–F4 patients (Sn. 74% and 77%; Sp. 76% and 76%), respectively. To predict F1–F4 compared to F0, the cutoff value was 0.34 (Sn. 68%, Sp. 75%) for APRI, while the cutoff value for FIB was 0.87 (Sn. 72%, Sp. 75%). The findings suggest that FIB-4 shows better diagnostic accuracy than APRI. Conclusion: This study provides optimal cutoff values for different groups of fibrosis patients for both serum markers. Also, the diagnostic accuracy of FIB-4 for predicting liver fibrosis was found to be superior to APRI in all disease stages.